2021
DOI: 10.1002/rra.3802
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal fluctuations of coarse particulate organic matter transport in a snowmelt‐dominated stream

Abstract: We measured coarse particulate organic matter (CPOM) transport along a wood-rich, pool-riffle mountain stream in the Southern Rockies of Colorado, USA, to examine how spatial variations in storage features and temporal variations in discharge influence the transport of CPOM. Ecologists have found that the majority of annual CPOM export occurs during periods of high discharge. More recently, geomorphologists have begun to examine the transport of CPOM as bedload. There has been, however, little direct sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…We did not sample CPOM transport rate overnight in either stream because after assessing discharge trends at each site, we found relatively little 24-h variability in flow. In addition, other studies have found that the diurnal cycle does not significantly impact CPOM transport (Marshall et al, 2021).…”
Section: Field Data Collectionmentioning
confidence: 94%
See 4 more Smart Citations
“…We did not sample CPOM transport rate overnight in either stream because after assessing discharge trends at each site, we found relatively little 24-h variability in flow. In addition, other studies have found that the diurnal cycle does not significantly impact CPOM transport (Marshall et al, 2021).…”
Section: Field Data Collectionmentioning
confidence: 94%
“…Coarse particulate organic matter (CPOM) is an important component of stream ecosystems (Fisher and Likens, 1973;Vannote et al, 1980) and watershed carbon cycling (Turowski et al, 2016). The composition and origin of CPOM varies, with CPOM particles ranging from autochthonous algal and plant fragments to allochthonous woody material (e.g., very small wood pieces, twigs), leaves, fruits, and coniferous needles and cones (Bunte et al, 2016;Iroumé et al, 2020;Gaillard et al, 2021;Marshall et al, 2021). Here, we define CPOM as organic matter 1-100 mm in diameter that does not meet the criteria of small wood, as defined by Galia et al (2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations